Development of "Triangle Pastle" D'croquette as a Culinary Business Assisted by Milkshake Media to Improve Students' Entrepreneurial Spirit in the Era of Industrial Revolution 4.0 - Fityahti Hilya Utami; Erita M. Lumbanbatu; Meutia Farani Aziz; Siti Rohayati (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2023)
Pastel is a snack that is usually a semicircle filled with meat and vegetables and served as a dessert or snack. D' croquette “triangle pastry” is a modification of the usual form and filling of pastels. This study aims to find out how the development of d'croquette as a culinary business assisted by milkshake media can increase the entrepreneurial spirit of students, especially physics education students. The results of the study show that d'croquette business development is able to increase the entrepreneurial spirit of students. The technique used in the “triangle pastry” d'croquette marketing process is using social media, especially milkshakes. From this research, it is hoped that it can grow and improve the entrepreneurial spirit of students in the era of the industrial revolution 4.0